Examination of nonlocal screening effects on protein crystallization - Hopkins, Sawyer S. (Kansas State University, 2017)
Over twenty percent of amino acids are ionized under biological conditions, and the subsequent electrostatic interactions have substantial effect on protein crystallization, binding, catalyzation, and recognition. These electrostatics along with other intermolecular forces create a delicate balancing act of repulsive and attractive forces. This thesis explores the effects of electrostatics on the formation of dense ordered structures. In dense protein aggregates the repulsive electrostatics are dominated by the entropic cost of compressing salt ions in the electrostatic screening layer. A non-local electrostatic interaction was derived to describe this behavior, and was used to examine the interplay of attractive energies and repulsive entropy on protein colloid stability and the crystallization process. Using a simple analytical model it was predicted that the derived electrostatic effects describe a finite window in phase space in which crystallization can occur. This simple model was expanded upon via computational methods simulating hard spherical particles aggregating under short-ranged attractive interactions and the repulsive electrostatics. From the computational simulations phase and dynamical data was extracted to confirmed the initial insight of the analytical model. The simulations also introduced new information not described by the simple model, most notably a metastable amorphous phase caused by the competition of energies and entropies.
Keywords: Protein; Computational simulation; Molecular dynamics